2004
DOI: 10.1200/jco.2004.10.184
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer Surgery: Morbidity and Mortality Results From a Prospective Randomized Controlled Trial Comparing D2 and Extended Para-Aortic Lymphadenectomy—Japan Clinical Oncology Group Study 9501

Abstract: Specialized surgeons could safely perform gastrectomy with D2 lymphadenectomy in patients with low operative risks. Para-aortic lymphadenectomy could be added without increasing major surgical complications in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
403
4
21

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 629 publications
(463 citation statements)
references
References 20 publications
28
403
4
21
Order By: Relevance
“…Although 5·8 per cent of the patients (6 of 104) died in hospital from disease progression during the primary admission, none died from postoperative complications. The 30‐day postoperative mortality rate of 1·9 per cent was acceptable in comparison with the rate of 0·8 per cent associated with elective potentially curative surgical oncology procedures for advanced gastric cancer in Japan32. Given the low rates of postoperative morbidity and mortality in the present study, the extent to which QoL was impaired by the operation is likely to have been small.…”
Section: Discussionmentioning
confidence: 59%
“…Although 5·8 per cent of the patients (6 of 104) died in hospital from disease progression during the primary admission, none died from postoperative complications. The 30‐day postoperative mortality rate of 1·9 per cent was acceptable in comparison with the rate of 0·8 per cent associated with elective potentially curative surgical oncology procedures for advanced gastric cancer in Japan32. Given the low rates of postoperative morbidity and mortality in the present study, the extent to which QoL was impaired by the operation is likely to have been small.…”
Section: Discussionmentioning
confidence: 59%
“…40 In recent years, there have been advances in the surgical approach with combining gastrectomy with limited lymphadenectomy in a Western setting 41 and D2 lymphadenectomy in an Asian setting 42 and the use of preoperative chemotherapy to increase the R0 resection rate. 43 It has also been shown that combination chemotherapy significantly improves survival compared to single agent 5-fluorouracil, however, at the expensive of increased toxicity.…”
Section: Presence Of Metastases (M)mentioning
confidence: 99%
“…Albeit recent advancements in surgical techniques and perioperative care, the postoperative morbidity rate is as high as approximately 40% after esophageal cancer surgery,1, 2 and 20–30% after both gastric cancer surgery3, 4, 5 and colorectal surgery 6, 7, 8. Various reports have shown that such postoperative complications frequently reduce the overall survival (OS) as well as cancer‐specific survival after major surgery for cancer 9.…”
Section: Introductionmentioning
confidence: 99%